Aggressive disseminated Rhizomucor pusillus infection in a Ph-like acute lymphoblastic leukemia patient: Early detection by cell-free DNA next-generation sequencing. Issue 3 (March 2022) - Shi, Liming; Zhao, Xiaoxia; Yan, Xu; Liu, Yu; Liu, Yong; Cao, He; Su, Keju; Wang, Cong; Gao, Sujun; Liu, Qiuju
Abstract: Disseminated Rhizomucor pusillus infection is a very rare but fatal complication in immunocompromised patients, because of aggressive clinical process with delayed diagnosis by routine laboratory tests. Recently, cell-free DNA next-generation sequencing (cfDNA NGS) has been used for the timely detection of infectious pathogens including mucormycosis. Herein, we described an 18-year-old male with Philadelphia-like acute lymphoblastic leukemia who received a timely diagnosis of R. pusillus infection by cell-free DNA next-generation sequencing, and confirmed by silver staining and qPCR on biopsy tissue. To the best of our knowledge, this was the first case of disseminated R. pusillus infection detected by cfDNA NGS and confirmed by histology in an adult leukemia patient. In addition, this case was supposed to be the most extensive R. pusillus infection diagnosed, involving the lung, skin, liver, kidney, spleen and brain, and the only one case who survived the infection had a favorable outcome through treatment with liposome amphotericin B sequential posaconazole. This case suggested that cfDNA NGS could be used to successfully detect rare pathogen infections, and this was especially important for R. pusillus because timely diagnosis and effective treatment could improve the prognosis of this kind of patient.